Survey Pekerja Sektor Informal Dan Sektor Formal Era Revolusi Industri di Kota Mataram - Satarudin Satarudin; Suprianto Suprianto; Sujadi Sujadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This research takes the title "Survey of Informal Sector Workers and the Formal Sector of the Industrial Revolution Era in Mataram City. The research objective was to analyze the income and welfare level of informal and formal sector workers era revolution industry in the city of Mataram. The research method was carried industut by means of a survey by taking a sample of 90 respondents, and the determination of the respondents was determined purposively by looking at the characteristics of the two workers. Overall, if the analysis of the income of informal and formal workers is related to the welfare level of the Sayogyo criteria with a rice equivalent, the category of near-poor is 10%, with an expenditure / capita / year of 450. kg equivalent value of rice / year. Meanwhile, 40% (36 respondents) were at the sufficient threshold with a per capita / year expenditure of 481-960 kg as a result of analysis an average of 750 kg equivalent to rice. The average per capita income of formal and informal workers is IDR 11.2550.000, - if divided by the price of rice during the study of IDR 10,000 per kg, the result is that 1.125 kg of rice means that almost 50% of the workers are in a decent life, consisting of 35 respondents. formal workers and 10 respondents to informal workers.